2016
DOI: 10.1177/1535370216629011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of proline in the treatment of menopause

Abstract: The amino acids in the placenta have multiple functions; however, the therapeutic effects of proline remain poorly for relief postmenopausal symptoms. The aim of present study was to evaluate the effects of proline in the treatment of menopause using in vitro and in vivo models. We assessed the therapeutic effects and regulatory mechanisms of proline by using MCF-7 estrogen-dependent cells, MG63 osteoblast cells, and ovariectomized mice model. An in vivo study was carried out in eight-weekold sham and ovariect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The GC-MS result shows in Table 4 ; methyl-proline and L-proline were increased during OVX and recovered after administration of tamoxifen and R. officinale root extract. This result was similar to that of other researchers;[ 28 29 ] these amino acids increased, indicating that bone collagen type 1 synthesis increases the density of bone.…”
Section: Discussionsupporting
confidence: 92%
“…The GC-MS result shows in Table 4 ; methyl-proline and L-proline were increased during OVX and recovered after administration of tamoxifen and R. officinale root extract. This result was similar to that of other researchers;[ 28 29 ] these amino acids increased, indicating that bone collagen type 1 synthesis increases the density of bone.…”
Section: Discussionsupporting
confidence: 92%
“…However, we found that the serum threonine level was positively associated with BMD among young women. Stachydrine is a derivative of proline, which has shown a beneficial effect on enhancing BMD through increasing serum estradiol and alkaline phosphatase levels and decreasing serum luteinizing hormone in OVX mice [ 37 ]. Formylkynurenine is a metabolite of the essential amino acid tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…In ovariectomized mice, oral proline administration reduced body weight and luteinizing hormone levels, increased estradiol and alkaline phosphatase levels, and improved bone mineral density. The authors suggested proline as a promising option for menopause treatment [49].…”
Section: Discussionmentioning
confidence: 99%